Nanocomposite tubes for magneto-active devices - V. Guarino; V. Iannotti; G. Ausanio; L. Ambrosio; L. Lanotte (eXPRESS Polymer Letters)
Small polymeric ducts incorporating a ribbon-shaped mat of densely packed magnetic nanofibers have been manufactured via electrospinning by using a cylindrical manifold, alternately under rotation or static. The magnetic nanofibers mat is located on the side of the tube and aligned to the longitudinal axis using the assistance of a magnetic field. The designed methodology ensures that the magnetic particles are completely wrapped into a protective polymer shell. Experimental results demonstrate that the innovative confinement of magnetic nanofibers, forming a longitudinal ribbon on a tube side, confers a high and reversible transverse strain under a moderate magnetic field stimulus: a magnetic field gradient ≤30 mT/mm, at a basic field intensity <0.04 T, induces a 40% decrement of the duct radius aligned with the magnetic force axis. In perspective, this is very attractive to fabricate magneto-active ducts suitable for microfluidic components, as well as biomedical devices to be applied in surgery and endoscopy.